간세포암 환자의 치료에 있어 수술적 절제술과 간동맥 화학색전술 치료요법에 따른 생존율 비교 연구 - 이광현 (The Graduate School, Ajou University, 2006)
ABSTRACT Comparative Study of the Survival Rates between Surgical Resection and Transcatheter Arterial Chemoembolization for the Patients with Hepatocellular Carcinoma Kwang Hyeon Lee Graduate School of Public Health Ajou University (Supervised by professor Ki Hong Jun) Background/Aims : The prognosis of hepatocellular carcinoma has been improved rapidly due to the recent advancement of various imaging tests and operative techniques. However, as the rate of early detection of hepatocellular carcinoma is still low, the percentage of cases of hepatocellular carcinoma diagnosed with advanced cancer with very poor prognosis remains high in reality. At an early stage of hepatocellular carcinoma, it can be treated adequately using operative or non？]operative methods, or the survival rates of the patients could be increased. This study attempted to investigate the stages of the patients with hepatocellular carcinoma at the first diagnosis along with their liver functions, and the differences in the survival rates and survival periods between the group who underwent surgical resection and the Transcatheter Arterial Chemoembolization group who treated with transcatheter arterial chemoembolization (TACE) which was a non？]operative method were investigated and compared. Further, statistical significances in the survival periods were examined by controlling prognostic factors affecting the survival rates of the patients with hepatocellular carcinoma. Material and Method : The subjects of this study were 192 patients diagnosed with primary hepatocellular carcinoma and treated for the disease between January 1, 2001 and December 31, 2004 at Ajou University Hospital. When the diagnosis of hepatocellular carcinoma was firstly made, their stages and Child？]Pugh classification were examined, the survival rates of hepatocellular carcinoma patients according to the treatment methods were calculated, and after controlling the prognostic factors which might affect the survival rates of the patients, its relations to survival periods were investigated. Result : Mean age of the 192 patients was 57 years, and the number of male patients was 3.2 times greater than that of female patients. Survived patients until December 31, 2004, the end of follow？]up period, were 85 (44.3%) and the number of patients died was 107 (55.7%). Of the total subject patients, the 1, 2, and 3 year survival rates were to be 56.4%, 42.0%, and 35.8%, respectively, and median survival period was 18 months. When it was looked into according to the treatment methods, the patient group who underwent surgical resection (86 people) accounted for 44.8%; their 1, 2, and 3 year survival rates were to be 77.7%, 67.5%, and 64.4%, respectively, with median survival period of 16 months. For the group who had TACE (106 people), these patients accounted for 55.2% of the total patients, and the 1, 2, and 3 year survival rates were 40.1%, 25.0%, and 18.9%, respectively, and median survival period was 7 months. Taken together, the median survival period of the surgical resection group was 9 months longer than that of the TACE group (P<0.001). In addition, among the patients who underwent surgical resection, Child？]Pugh classes A, B and C groups accounted 57%, 38%, and 5%, respectively. With regard to the survival rates according to treatment methods of the Child？]Pugh Class A group, in which their liver function was adequate for operation, no statistically significant difference(P=0.0817) in survival rates was found between the surgical resection group and the TACE group among patients included the stage ？Tand ？Ugroups, also the stage ？V group showed no significant differences in the survival rates (P=0.2377); the results can be concluded that there are no statistically significant differences in the survival rates according to treatment methods if the patients with hepatocellular carcinoma maintain good liver function and remain in an early stage. In the results of the analysis of the survival rates according to the modified UICC staging, the survival rates of the surgical resection group were higher than that of the TACE group, and there were statistically significant differences in the survival rates according to treatment methods among the different stage groups(P<0.001), showing that the survival rates and survival periods of the patients with hepatocellular carcinoma were statistically significantly lower with their stages increased. Significant prognostic factors in the survival rate of hepatocellular carcinoma were found to be treatment methods, liver cirrosis, Child？]Pugh Class, serum alpha？]fetoprotein (AFP), the presence or absence of serum ascites, the Modified UICC staging, and so on. In the analysis conducted after controlling the above variables, there were statistically significant differences between the treatment methods of surgical resection and TACE. Conclusions : In most cases, the treatment of hepatocellular carcinoma was attempted in limited cases where liver function was intact, and there were no statistically significant differences in the survival rates according to treatment methods if the patients with hepatocellular carcinoma maintain good liver function and remain in an early stage. In expecting survival rate, the degree of liver function and stages of the cancer were found to be significant prognostic factors. In regard to the differences in survival rates between the TACE group in which the subjects had advanced cancers so that operation was not possible and the surgical resection group, the survival period of the surgical resection group was found to be longer than that of the TACE group. ---------------------------------------------------------------- Key words : Hepatocellular carcinoma, Survival rate, Stage, Child-Pugh class, Surgical resection, Transcatheter Arterial Chemoembolization(TACE)
학위논문(석사)--아주대학교 보건대학원 :보건학과,2006. 8